Evaluation of the Electronic Structure Resulting from ab-initio Calculations on Simple Molecules Using the Molecular Orbital Theory - Samuel E P P Masan; Fitri N Febriana; Andi H Zaidan; Ira Puspitasari; Febdian Rusydi (Postgraduate, University of Mataram, 2021)
Hartree Fock (HF) and Density Functional Theory (DFT) have been commonly used to model chemical problems. This study uses the Molecular Orbital Theory (MOT) to evaluate the electronic structure of five diatomic molecules generated by HF and DFT calculations. The evaluation provides an explanation of how the orbitals of a molecule come to be and how this affects the calculation of the physical quantities of the molecule. The evaluation is obtained after comparing the orbital wave functions calculated by MOT, HF, and DFT. This study found that the nature of the Highest Occupied Molecular Orbital (HOMO) of a molecule is determined by the valence orbital properties of the constituent atoms. This HOMO property greatly influences the precision of calculating the molecular electric dipole moment. This shows the importance of understanding the orbital properties of a molecule formed from the HF and DFT calculations